For the Evaluation of Pacific Island Athletes, an ECG and Echocardiography Are Highly Recommended - Jean-Claude Chatard (Hearts, 2021)
Physical exercise increases the relative risk of sudden cardiac death (SCD) in athletes when compared to a non-sporting population. Pre-participation evaluation (PPE) of athletes is thus of major importance. For Pacific Island athletes, medical guidelines recommend an echocardiography to complement a PPE including personal and family history, a physical examination and a resting twelve-lead electrocardiogram (ECG). Indeed, silent rheumatoid heart diseases found in up to 7.6% of adolescents give rise to severe valve lesions, which are the main causes of SCD in Pacific Island athletes. This short review examines the incidence rate of SCD in Pacific Island athletes and indicates how a questionnaire, physical examination, ECG and echocardiography can prevent it.